Nuclear Transfer using Human CD59 and IL-18BP Double Transgenic Fetal Fibroblasts in Miniature Pigs - Junghyun Ryu; Minjeong Kim; Jin Seop Ahn; Kwang Sung Ahn; Hosup Shim (The Korean Society of Animal Reproduction and Biotechnology, 2016)
Xenotransplantation involves multiple steps of immune rejection. The present study was designed to produce nuclear transfer embryos, prior to the production of transgenic pigs, using fibroblasts carrying transgenes human complement regulatory protein hCD59 and interleukin-18 binding protein (hIL-18BP) to reduce hyperacute rejection (HAR) and cellular rejection in pig-to-human xenotransplantation. In addition to the hCD59-mediated reduction of HAR, hIL-18BP may prevent cellular rejection by inhibiting the activation of natural killer cells, activated T-cell proliferation, and induction of IFN-γ. Transgene construct including hCD59 and ILI-18BP was introduced into miniature pig fetal fibroblasts. After antibiotic selection of double transgenic fibroblasts, integration of the transgene was screened by PCR, and the transgene expression was confirmed by RT-PCR. Treatment of human serum did not affect the survival of double-transgenic fibroblasts, whereas the treatment significantly reduced the survival of non-transgenic fibroblasts (p<0.01), suggesting alleviation of HAR. Among 337 reconstituted oocytes produced by nuclear transfer using the double transgenic fibroblasts, 28 (15.3%) developed to the blastocyst stage. Analysis of individual embryos indicated that 53.6% (15/28) of embryos contained the transgene. The result of the present study demonstrates the resistance of hCD59 and IL-18BP double-transgenic fibroblasts against HAR, and the usefulness of the transgenic approach may be predicted by RT-PCR and cytolytic assessment prior to actual production of transgenic pigs. Further study on the transfer of these embryos to surrogates may produce transgenic clone miniature pigs expressing hCD59 and hIL-18BP for xenotransplantation.